BEKERJA DI BANK KONVESIONAL MENURUT FIKIH EKONOMI - Azwar, Yuzakki (EQUILIBRIUM, 2019)
This study examines the law of working on Conventional Banks according to economic fiqh, in society there is a different view of people who earn a living on Conventional Banks. For some people there is a personal conflict in responding to the law of working in a conventional bank. On the other hand, it works in a conventional bank, although it contains goodness, but it cannot be separated from the interest that the fatwa of the Indonesian Ulema Council (MUI) is categorized as usury. This study was conducted through field research with qualitative analysis methods. Data was collected through interviews with informants working in conventional banks. This field data is reviewed according to the economic fiqh perspective. The results of this study conclude that the law of working at a conventional bank according to economic fiqh is changing if to fulfill the necessities of life in the framework of maslahah which are still Ad-Dharuriyyah and during their activities are still halal and help fellow human beings but haram otherwise.